2022
DOI: 10.3390/antiox11040673
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Glutathione Helps to Mitigate Mycobacterium tuberculosis Infection in the Lungs

Abstract: Mycobacterium tuberculosis (M. tb), the causative agent of tuberculosis (TB), is responsible for causing significant morbidity and mortality, especially among individuals with compromised immune systems. We have previously shown that the supplementation of liposomal glutathione (L-GSH) reduces M. tb viability and enhances a Th-1 cytokine response, promoting granuloma formation in human peripheral blood mononuclear cells in vitro. However, the effects of L-GSH supplementation in modulating the immune responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Indeed, significantly reduced levels of GSH were found in the plasma and immune cells of patients with pulmonary TB [37]. Furthermore, supplementation of GSH was shown to improve Mtb killing by macrophages in vitro and in model animals [38,39]. In this study, we observed a significant reduction in two GSH pathway enzymes, GR and GSTM3, in the lungs of Mtb-infected humanized mice.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, significantly reduced levels of GSH were found in the plasma and immune cells of patients with pulmonary TB [37]. Furthermore, supplementation of GSH was shown to improve Mtb killing by macrophages in vitro and in model animals [38,39]. In this study, we observed a significant reduction in two GSH pathway enzymes, GR and GSTM3, in the lungs of Mtb-infected humanized mice.…”
Section: Discussionsupporting
confidence: 53%
“…One strategy for GSH supplementation during oxidant stress is oral LGSH, which has been shown to decrease oxidant stress in HIV subjects and patients with type 2 diabetes [32][33][34]. In a mouse model of an active Mycobacterium tuberculosis infection, GSH depletion exacerbated the pathogen burden, but oral LGSH decreased both pulmonary oxidant stress and granuloma-promoting immune responses, resulting in decreases in the pulmonary bacterial infection [58]. Similar results were obtained in a diabetic mouse model with an active Mycobacterium tuberculosis infection, demonstrating that oral LGSH treatments can also improve bacterial clearance in an immunocompromised model [59].…”
Section: Discussionmentioning
confidence: 99%
“…Th1 activated mononuclear phagocytes (MP) as well as produced IL-12 to promote Th1-type cellular immune responses ( 52 ). IL-12, a polarizing cytokine, induces CD4 T cells to differentiate into a Th1 subset by two-stage differentiation a) IL-12 induces the outgrowth of IFN-γ Th1 cells, b) about half of Th1 cells ultimately gain CX3CR1 expression and exhibit a cytotoxic effector profile depending on the transcription factor ZEB2, which, in turn, produces IL-2 and IFN-γ ( 53 , 54 ). IFN-γ-dependent macrophage activation is important for bactericidal functions.…”
Section: Discussionmentioning
confidence: 99%